Systematic Management of Morality Development in Strengthening Elementary School Character Education - Wawan Wawan; Eva Dianawati Wasliman (Papanda Publisher, 2026)
Character education constitutes a fundamental mandate in contemporary education systems, yet systematic management approaches remain insufficiently examined. This study investigates morality development management in strengthening character education at elementary schools facing resource constraints. Employing qualitative case study design, this research examined SDN Tegalmerak and SDN Pagermaneuh in Tanggeung District through interviews with principals, teachers, students, and parents (n=52), participatory observations, and documentation analysis. Data were analyzed using Miles, Huberman, and Saldaña's interactive model, applying George R. Terry's management framework. Findings reveal systematic implementation across four management functions: (1) collaborative planning integrating character values into curriculum and activities; (2) clear organizational structures with specialized coordination teams; (3) diverse implementation strategies including religious habituation, teacher role modeling, and extracurricular engagement; and (4) multi-layered monitoring through classroom observations and stakeholder feedback. Measurable improvements included increased attendance (87% to 94%), reduced disciplinary incidents (43% decrease), and spontaneous moral behavior demonstration by 78% of students. However, students with strong parental involvement showed 67% greater behavioral improvements, underscoring ecological factors' critical role. Results validate classical management theory's applicability to character education while revealing that effectiveness depends substantially on home-school value consistency rather than school efforts alone. Findings suggest character education requires coordinated multi-stakeholder approaches addressing resource constraints through adaptive strategies.